Nanogenerators Begin to Light Up: A Novel Poling‐Free Piezoelectric System with Multicolor Photoluminescence as an Efficient Mechatronics Development Platform. Issue 19 (19th July 2018) - Ma, Songyuan; Jin, Long; Huang, Xi; Riziotis, Christos; Huang, Rui; Zhang, Chaoliang; Lu, Jun; Yang, Weiqing
Abstract: In this work, a novel design of poly (vinylidene fluoride)/carbon quantum dots (PVDF/CQDs) based flexible poling‐free hybrid material system able to efficiently convert small amounts of mechanical energy into electricity through the intrinsic piezoelectric nanostructures is reported. The PVDF/CQDs composite is fabricated through solution casting followed by a high‐pressure crystallization process. The introduction of 3D quasi‐spherical CQDs has in situ induced the self‐assembly of polymorphic substructures in the PVDF crystallites at high pressure, and piezoelectric 3D nanosheet arrays, 1D nanometer small sticks, and 1D nanowires, respectively, are formed in situ with the increase of CQDs concentration. Without any electrical polarization treatment, the maximum open‐circuit voltage output density of the durable composite system reaches 19.2 V cm −2 and short‐circuit current output density of 550 nA cm −2, both far exceeding that of pure PVDF. Simultaneously, owing to the successful incorporation of CQDs, the material shows excellent fluorescent effect with high stability, and its multicolor photoluminescence is well retained even after the endurance for a rigorous treatment at high pressure and high temperature. The as‐developed environmental friendly PVDF/CQDs compound may diversify niche applications in a new‐generation of self‐powered autonomous optoelectronic devices, biosensors, cell imaging, and so on. Abstract : A novel poling‐free piezoelectric hybrid polymeric system, with hyperstable multicolour photoluminescence and ultrahigh mechanical‐to‐electrical conversion, is designed and fabricated. The maximum open‐circuit voltage output density of the durable system reaches 19.2 V cm −2, surpassing that of state‐of‐the‐art piezopolymers reported to date, and its fluorescence properties are retained even after the endurance for a rigorous treatment at high pressure and high temperature.